2016
DOI: 10.1248/cpb.c16-00033
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Levels of Phenylethanoid Glycosides, Antioxidant Activity, and Other Quality Traits in <i>Cistanche deserticola</i> Slices by Steam Processing

Abstract: We investigated the effect of steaming time on Cistanche deserticola Y. C. MA slices by analyzing levels of bioactive compounds, antioxidant activity, and weight loss compared with fresh, directly oven-dried, and blanched samples. Fresh samples had extremely low levels of phenylethanoid glycosides and antioxidant activity. Lower levels of weight loss and higher amounts of soluble sugars, polysaccharides, and dilute ethanolsoluble extracts were found when the slices were steamed rather than blanched. Slices ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
(17 reference statements)
2
14
1
Order By: Relevance
“…Studies have shown that the antioxidant activity of C. tubulosa was ABTS•+ 1.39 mM TEAC/g and FRAP 1.61 mM FEAC/g respectively (Xiong et al, 2013). In other studies, the maximum free radical scavenging activity as defined in the DPPH test was 23.08 μmol TE/g FW and FRAP was 11.68 μmol TE/g (Peng et al, 2016). The antioxidant property of the dried flowers of P. tournefortii was much higher compared to these studies.…”
Section: Resultsmentioning
confidence: 88%
“…Studies have shown that the antioxidant activity of C. tubulosa was ABTS•+ 1.39 mM TEAC/g and FRAP 1.61 mM FEAC/g respectively (Xiong et al, 2013). In other studies, the maximum free radical scavenging activity as defined in the DPPH test was 23.08 μmol TE/g FW and FRAP was 11.68 μmol TE/g (Peng et al, 2016). The antioxidant property of the dried flowers of P. tournefortii was much higher compared to these studies.…”
Section: Resultsmentioning
confidence: 88%
“…Given C. deserticola was usually employed to deal with kidney deficiency in Chinese folk medicine, which implied this edible medicinal herb can be regarded as promising alternative agent to intervene osteoporosis based on the theory of “kidney dominate bone” (Wang et al, 2016). Published data had proved the anti-osteoporotic effect of C. deserticola extracts both in vivo and in vitro (Liang et al, 2011; Li et al, 2012; Liang et al, 2013; Xu et al, 2017; Song et al, 2018), and several isolated compounds including echinacoside (Li et al, 2013), acteoside (Lee et al, 2013), and cistanoside A (Xu et al, 2017) which also had been reported processing anti-osteoporotic activities; and other compounds like 2’-acetylacteoside was confirmed possessed antioxidant, anti-inflammatory, neuroprotective, hepatoprotective, immune-enhancing (Li et al, 2016), and anti-aging potentials (Peng et al, 2016). To date, dozens of bioactive phenylethanoid glycosides have been identified from Cistanche herb (Wang et al, 2012), echinacoside, and acteoside are the main compounds existing in most of the Cistanche species with the contents were 1.83–41.49 and 0.27–8.28 mg/kg, respectively; whereas the other phenylethanoid glycosides including 2’-acetylacteoside, 6’-acetylacteoside, cistanoside A, cistanoside C, and isoacteoside were 1.56–3.16 mg/g, 0.49–1.66 mg/kg, 1.41–10.11 mg/kg, 0.33–2.24 mg/kg, and 0.08–5.00 mg/kg, respectively (Dong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As previously described (Jiang and Tu, 2009), TGs contain lots of bioactive compounds, for example echinacoside, tubuloside A, acteoside, isoacteoside and 2'-acetylacteoside, and some of them showed neuroprotective functions after cerebral I/R injury (Peng et al, 2016). Echinacoside has lots of pharmacological effects, such as antioxidation, anti-senescence, neuroprotection, anti-inflammation, promotion of cicatrization, hepatoprotection, promotion of bone formation and anti-tumor activities (Yu et al, 2016;Li et al, 2018;Ji et al, 2019;Xu et al, 2019).…”
Section: Discussionmentioning
confidence: 87%